Differentiation of multi-metal ions based on fluorescent dual-emission carbon nanodots1. Issue 100 (29th October 2015) - Qu, Fei; Wang, Shuai; Liu, Dongya; You, Jinmao
<x xml:space="preserve">Abstract</x> The different functional groups on dual-emission carbon nanodots play a vital role in the differentiation of multi-metal ions.